Highly effective biosynthesis of N-acetylated human thymosin β4 (Tβ4) in Escherichia coli. (12th November 2018) - Yu, Rui; Cao, Sai; Liu, Yanhong; Si, Xinxi; Fang, Ting; Sun, Xu; Dai, Hongmei; Xu, Junjie; Fang, Hongqing; Chen, Wei
Abstract: Thymosin β4 (Tβ4) is a multifunctional N -acetylated peptide with distinct activities important at various stages. Due to its potential multiple therapeutic uses in many fields, there is an increasing need of Tβ4 at lower costs than with the use of chemical synthesis. In this research, we developed a method to produce rhTβ4 with N -acetylation in E. coli . Firstly, the E. coli strain whose chromosome being integrated by the specific N-terminal acetyltransferase ssArd1 was constructed. Secondly, the rhTβ4-Intein was constructed, in which rhTβ4 was fused to the N-terminus of the smallest mini-intein Spl DnaX. The rhTβ4 could be fully acetylated when the rhTβ4-Intein was expressed in the engineering strain. After purification, the rhTβ4-Intein fusion protein was induced with dithiothreitol (DTT) to release rhTβ4 through intein-mediated N-terminal cleavage. Under the optimal conditions, the N-terminal serine residue was shown to be 100% acetylated and the yield of N -acetylated rhTβ4 can reach 200 mg per litre. The N -acetylated rhTβ4 could be stable at 2–8 °C for 24 months in PBS buffer without protein degradation and concentration change. The N -acetylated rhTβ4 also showed the activity of binding with actins from different sources and excellent therapeutic effect on the rats with moderate to severe dry eye disease.